ОЦІНЮВАННЯ НЕВИЗНАЧЕНОСТІ ВИМІРЮВАННЯ ЕЛЕКТРОЕНЕРГІЇ ПРИ ЗНИЖЕНОМУ СТРУМІ ЧЕРЕЗ ВУЗОЛ ОБЛІКУ - ВАСИЛЕЦЬ, СВЯТОСЛАВ; ВАСИЛЕЦЬ, КАТЕРИНА; ІЛЬЧУК, ВОЛОДИМИР (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Обґрунтовано математичну модель для оцінювання невизначеності вимірювання електроенергії при зниженому струмі через вузол обліку. Встановлено, що на точність обліку трифазним лічильником трансформаторного ввімкнення впливають характеристики кожного з вимірювальних каналів, що відповідають фазам. Запропоновано для оцінювання невизначеності вимірювання електроенергії використовувати нечітку функцію, аргументами якої є фазні струми споживача. Реалізація моделі у вигляді комп’ютерної програми дозволяє удосконалити програмне забезпечення смарт лічильників електроенергії. The object of the study is the process of electricity measurement by a three-phase metering unit, which includes an electricity meter and measuring current transformers in 0.38 kV distribution networks. The subject of the study is the uncertainty of electricity measurement at a reduced current through the metering unit. The aim of the research is to increase the accuracy of electricity measurement by a smart meter due to the development of a mathematical model for estimating the uncertainty of measurement at reduced current through the metering unit. During the research, the theory of fuzzy sets, methods of polynomial approximation, in particular, the method of least squares, the method of minimizing the Chebyshev norm of the discrepancy were used. As a result of the study, a mathematical model was obtained for estimating the uncertainty of electricity measurement by the metering unit in the reduced load mode using a fuzzy function. The model differs from the known ones by taking into account the influence of the values ​​of asymmetric currents of the load phases at the boundaries of the fuzzy interval at the limit level of confidence that characterizes the measurement result. A method of calculating the parameters of the fuzzy function and the limit level of confidence for the metering unit of a specific configuration has been developed, which involves evaluating the deviations of the readings of the transformer connection meter from the readings of the additional direct connection meter. The model is implemented as a computer program. Based on the current meter readings, which are read automatically, the largest amount of underaccounting is calculated. This makes it possible to provide the consumer with recommendations on the modernization of the metering unit equipment, in particular, the replacement of current transformers, in order to bring their transformation ratio into compliance with the actual load currents and, accordingly, work in the normalized range.
Keywords: електроенергія; лічильник; вимірювання; невизначеність; трансформатор струму; споживач; вузол обліку